Stališča zdravstvenega osebja in bolnikov do uporabe računalnikov v ZD Brežice - Iljaž, Rade (Zdravniški vestnik, 2003)
Background. According to GINA guidelines asthmatic patients should be (nearly)without asthmatic symptoms, have minimal requirements for reliever, without limitations to daily activities and with appropriate quality of life. The upper mentioned goals of asthma therapy were not met in everyday life and a failure of the GINA expectations was confirmed by epidemiological studies. This study presents a management of adults and children with asthma in Slovenia. Methods. Patients with asthma were chosen at random from all regionsof Slovenia. 172 adults and 168 children with asthma filled in a questionnaire. Results. Our patients were prescribed inhaled glucocorticoid (85% of adults and 96% of children with asthma) in much greater segment than asthmatic patients in other countries. Still they had too many daily asthmaticsymptoms and experienced too frequent episodes of nocturnal asthma. Even trivial activities were significantly disturbed by asthma. Their quality of life was low. Our patients admitted low compliance with therapy with inhaled glucocorticoids. Conclusions. In spite of appropriate prescriptions ofinhaled glucocorticoids to asthmatic patients included in our study the goals of asthma therapy were not met. The most obvious reason for that failurewas low compliance to therapy with inhaled glucocorticoids. It is belived that intensive education programs for asthmatic patients and the medical personnel involved in the management of asthmatic patients should be proposed.
Keywords: Ambulantna oskrba; Ambulatory Care; ankete; Attitude To Computers; bolniki; Cross-Sectional Studies; health care; Health Manpower; Medical Records Systems, Computerized; Medicinske kartoteke, sistemi računalniški; Odnos do računalnikov; organizacija; organization; Presečne študije; Questionnaires; računalniki; Zdravstveni delavci; zdravstvo